Coordinated optimization of P2P energy trading and network operation for active distribution network with multi-microgrids - Peishuai Li; Yihan Wang; Tao Zheng; Yulong Jin; Weizhi Yuan; Wenwen Guo (Global Energy Interconnection)
Microgrids (MGs) and active distribution networks (ADNs) are important platforms for distributed energy resource (DER) consumption. The increasing penetration of DERs has motivated the development ADNs coupled with MGs. This paper proposes a distributed co-optimization method for peer-to-peer (P2P) energy trading and network operation for an ADN integrated with multiple microgrids (MMGs). A framework that optimizes P2P energy trading among MMGs and ADN operations was first established. Subsequently, an energy management model that aims to minimize the operation and energy trading costs was constructed for each MG. Accordingly, the MMGs’ cooperative game model was established based on Nash bargaining theory to incentivize each stakeholder to participate in P2P energy trading, and a distributed solution method based on the alternating direction method of multipliers was developed. Moreover, an algorithm that adjusts the amount of energy trading between the ADN and MG is proposed to ensure safe operation of the distribution network. With the communication between the MG and ADN, the MMGs’ P2P trading and ADN operations are optimized in a coordinated manner. Finally, numerical simulations were conducted to verify the accuracy and effectiveness of the proposed method.